2017
DOI: 10.1128/aem.01295-17
|View full text |Cite
|
Sign up to set email alerts
|

The Sortase-Dependent Fimbriome of the Genus Bifidobacterium: Extracellular Structures with Potential To Modulate Microbe-Host Dialogue

Abstract: Bifidobacteria are important gut commensals of mammals, including humans, of any age. However, the molecular mechanisms by which these microorganisms establish themselves in the mammalian gut and persist in this environment are largely unknown. Here, we analyzed the genetic diversity of the predicted arsenal of sortase-dependent pili of known and sequenced members of the Bifidobacterium genus and constructed a bifidobacterial sortase-dependent fimbriome database. Our analyses revealed considerable genetic vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 67 publications
0
41
0
2
Order By: Relevance
“…A very recent study showed these sortase-dependent pili to be ubiquitous in Bifidobacterium spp. and some coded for FimB subunits that were able to bind starch, xylan and pectin, indicative of a luminal location, while others showed interaction with the host [ 18 , 88 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A very recent study showed these sortase-dependent pili to be ubiquitous in Bifidobacterium spp. and some coded for FimB subunits that were able to bind starch, xylan and pectin, indicative of a luminal location, while others showed interaction with the host [ 18 , 88 ].…”
Section: Resultsmentioning
confidence: 99%
“…A specific set of Tad pili and sortase-dependent pili has been discovered in B . breve that are involved in intestinal persistence and the host-microbe dialogue [ 17 , 18 ]. Surface exopolysaccharides in B .…”
Section: Introductionmentioning
confidence: 99%
“…Pili or fimbriae are proteinaceous extracellular appendages produced by many bacteria, that protrude from the bacterial cell surface and that can be involved in microbe-host interactions promoting adhesion to the intestinal epithelium or facilitating aggregation with other bacterial cells (Scott and Zahner, 2006;Kline et al, 2010;Foroni et al, 2011). Two different types of pili have been described in bifidobacteria, i.e., sortase-dependent pili, and the type IVb pili, both of which are also known as tight adherence pili (Tad pili) (O'Connell Motherway et al, 2011;Milani et al, 2017b). Bifidobacterial sortase-dependent pili are not only responsible for adhesion and interaction with the host, but also are involved in the microbe-microbe interactions and in stimulation/modulation of the host immune system.…”
Section: Pili/fimbriaementioning
confidence: 99%
“…The Bifidobacterium genus currently consists of 56 species and 9 subspecies, members of which have been isolated from human, other mammalian, and certain insect intestinal contents (11,12). Recently, it has been demonstrated that members of the genus Bifidobacterium interact with other bacterial species and the host using extracellular structures, such as sortase-dependent pili and type IVb tight adherence (Tad) pili (13)(14)(15). Furthermore, extracellular anti-inflammatory proteins, such as the serine protease inhibitor (serpin) protein, were identified in several bifidobacterial species (16,17), as well as extracellular macromolecules, like exopolysaccharides (EPSs), which form a glycan slime layer that is loosely attached to the cell (18,19).…”
mentioning
confidence: 99%